Mapping the advancements in floristic knowledge of Italy (2005–2025) - Gianniantonio Domina; Gianluigi Bacchetta; Fabrizio Bartolucci; Marco D’Antraccoli; Lorenzo Peruzzi; Adriano Stinca; Alessandro Alessandrini; Liliana Bernardo; Francesco Boscutti; Daniela Bouvet; Maurizio Bovio; Giacomo Calvia; et al. (Plant Biosystems, 2026)
Based on the evaluation of 3,902 local floristic references published between 2005 and 2025, an update to the floristic knowledge map of Italy is presented. To measure the progress in floristic knowledge across Italy’s administrative regions, the ‘Index of Floristic Knowledge Advancement’ (IFA) is proposed here. This index categorizes regions based on the proportion of potential improvement that has actually been achieved. Results showed an improvement in knowledge, most notably for Northern and Central Italy. Emilia-Romagna emerged as the most comprehensively documented region with the highest IFA value (0.81), followed by Lombardia (0.60), Friuli-Venezia Giulia (0.54), Trentino-Alto Adige and Veneto (0.53). In central Italy, Lazio (0.50), Sardegna (0.45) and Toscana (0.36) registered the highest scores. Over the past twenty years, 453 specific and subspecific taxa have been described from the Italian territory, the majority of which (443) are Italian endemics. Hieracium is the most represented genus (147 taxa). The marked progress documented is likely due to the accelerated impact of coordinated scientific projects, citizen science programs, the development of digital databases, and an increased focus on taxonomic research.

Manufacturing 3D aortic root models for in vitro assessment of calcific aortic valve stenosis - Nicoletta Curcio; Luigi Bernardi; Antonio Rosato; Fabio Pappalardo; Martina Schembri; Michele Conti; Riccardo Vismara; Riccardo Gorla; Pietro Spagnolo; Lorenzo Menicanti; Alessandro Parolari; Giacomo Bortolussi; et al. (Annals of Biomedical Engineering, 2026)

The mite, the bug, and the nematode: Assessing the efficacy of three biological control agents against Echinothrips americanus (Thysanoptera: Thripidae) - Fabio Marino; Linda Abenaim; Giuseppe Conte; Daniele Marraccini; Priscilla Farina; Barbara Conti (Crop Protection, 2026)

The invasion history of Ambrosia psilostachya (Asteraceae) in Italy: first record and distribution over more than one century - Chiara Montagnani; Rodolfo Gentili; Gerhard Karrer; Sarah Caronni; Alicia Teresa Rosario Acosta; Michele Adorni; Alessandro Alessandrini; Nicola Maria Giuseppe Ardenghi; Gabriella Buffa; Fabrizio Bartolucci; Alessandra Belisario; Fabrizio Bonali; et al. (Plant Biosystems, 2025)

Weaponizing CRISPR/Cas9 for selective elimination of cells with an aberrant genome - Sara Tavella; Alessia di Lillo; Anastasia Conti; Fabio Iannelli; Alexandra Mancheno-Ferris; Valentina Matti; Raffaella Di Micco; Fabrizio d’Adda di Fagagna (DNA Repair, 2025)

CoMMa: A GIS geomorphometry toolbox to map and measure confined landforms - Riccardo Arosio; Joana Gafeira; Laurence H. De Clippele; Andrew J. Wheeler; Veerle A.I. Huvenne; Fabio Sacchetti; Luis A. Conti; Aaron Lim (Geomorphology, 2024)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

When solid recovered fuel (SRF) production and consumption maximize environmental benefits? A life cycle assessment - Navarro Ferronato; Chiara Giaquinta; Fabio Conti; Vincenzo Torretta (Waste Management, 2024)

Fully convolutional neural networks applied to large-scale marine morphology mapping - Riccardo Arosio; Brandon Hobley; Andrew J. Wheeler; Fabio Sacchetti; Luis A. Conti; Thomas Furey; Aaron Lim (Frontiers in Marine Science, 2023)
In this study we applied for the first time Fully Convolutional Neural Networks (FCNNs) to a marine bathymetric dataset to derive morphological classes over the entire Irish continental shelf. FCNNs are a set of algorithms within Deep Learning that produce pixel-wise classifications in order to create semantically segmented maps. While they have been extensively utilised on imagery for ecological mapping, their application on elevation data is still limited, especially in the marine geomorphology realm. We employed a high-resolution bathymetric dataset to create a set of normalised derivatives commonly utilised in seabed morphology and habitat mapping that include three bathymetric position indexes (BPIs), the vector ruggedness measurement (VRM), the aspect functions and three types of hillshades. The class domains cover ten or twelve semantically distinct surface textures and submarine landforms present on the shelf, with our definitions aiming for simplicity, prevalence and distinctiveness. Sets of 50 or 100 labelled samples for each class were used to train several U-Net architectures with ResNet-50 and VGG-13 encoders. Our results show a maximum model precision of 0.84 and recall of 0.85, with some classes reaching as high as 0.99 in both. A simple majority (modal) voting combining the ten best models produced an excellent map with overall F1 score of 0.96 and class precisions and recalls superior to 0.87. For target classes exhibiting high recall (proportion of positives identified), models also show high precision (proportion of correct identifications) in predictions which confirms that the underlying class boundary has been learnt. Derivative choice plays an important part in the performance of the networks, with hillshades combined with bathymetry providing the best results and aspect functions and VRM leading to an overall deterioration of prediction accuracies. The results show that FCNNs can be successfully applied to the seabed for a morphological exploration of the dataset and as a baseline for more in-depth habitat mapping studies. For example, prediction of semantically distinct classes as “submarine dune” and “bedrock outcrop” can be precise and reliable. Nonetheless, at present state FCNNs are not suitable for tasks that require more refined geomorphological classifications, as for the recognition of detailed morphogenetic processes.

Functional exercise capacity in maximal and submaximal activities of individuals with polio sequelae - Claudio Andre Barbosa de Lira; Fabio Carderelli Minozzo; Thalles Guilarducci Costa; Vinnycius Nunes de Oliveira; Gustavo Conti Teixeira Costa; Acary Souza Bulle Oliveira; Abrahão Augusto Joviniano Quadros; Rodrigo Luiz Vancini; Bolivar Saldanha Sousa; Antonio Carlos da Silva; Marilia Santos Andrade (European Journal of Applied Physiology, 2023)

Onobrychis alba subsp. calcarea (Fabaceae): typification of the name and first record for the Croatian flora - Fabio Conti; Fabrizio Bartolucci; Sandro Bogdanović; Adriano Stinca (Plant Biosystems, 2023)

Construction and demolition waste recycling in developing cities: management and cost analysis - Navarro Ferronato; Rocio Clara Fuentes Sirpa; Edith Gabriela Guisbert Lizarazu; Fabio Conti; Vincenzo Torretta (Environmental Science and Pollution Research, 2022)
In Bolivia, construction and demolition waste (CDW) is unmanaged. The current research implemented a CDW flow analysis and a cost assessment in the city of La Paz, aiming to compare future recycling scenarios. Lack of data is challenging; therefore, a review of 31 international studies has been conducted. Results report that the waste generation rate (WGR) of concrete residential buildings can be of about 91.9–113.3 kg m −2 for construction and about 867.2–1064.8 kg m −2 for demolition. In addition, positive correlation was found in national WGR with number of inhabitants and the GDP. By these results, it was estimated that about 271,051–349,418 tonnes of CDW are potentially generated yearly in La Paz, about two times more than the CDW projected by local authorities. By the scenarios analysis, it was estimated that 56.1–71.1% of the inert aggregates can be recycled. The cost of the system is estimated between 7.8 and 31.1 USD t CDW −1 , for a total annual cost (20 years horizon) of about 2.3–9 million USD y −1 depending on the management scenario. In the best scenario, an average fee of less than 1% of the current costs of a flat in La Paz can be required, potentially affordable for the local economy. The most attractive scenario involves the source separation of recyclable materials and the hybrid organization of stationary and mobile recycling facilities. Results show that a CDW management can be implemented in La Paz to foster a circular economy in developing cities.

Diachronic Observations Reveal Different and Scale-Dependent Response of Sand Dune Plants to Seashore Dynamics - Stefano Chelli; Fabio Conti; Luca Bracchetti (Estuaries and Coasts, 2022)

Clinical efficacy of different monoclonal antibody regimens among non-hospitalised patients with mild to moderate COVID-19 at high risk for disease progression: a prospective cohort study - Alessia Savoldi; Matteo Morra; Pasquale De Nardo; Anna Maria Cattelan; Massimo Mirandola; Vinicio Manfrin; Piergiorgio Scotton; Maria Teresa Giordani; Lucio Brollo; Sandro Panese; Massimiliano Lanzafame; Giovanna Scroccaro; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
This study aimed to compare the clinical progression of COVID-19 in high-risk outpatients treated with the monoclonal antibodies (mAb) bamlanivimab, bamlanivimab-etesevimab and casirivimab-imdevimab. This is an observational, multi-centre, prospective study conducted from 18 March to 15 July 2021 in eight Italian tertiary-care hospitals including mild-to-moderate COVID-19 outpatients receiving bamlanivimab (700 mg), bamlanivimab-etesevimab (700–1400 mg) or casirivimab-imdevimab (1200–1200 mg). All patients were at high risk of COVID-19 progression according to Italian Medicines Agency definitions. In a patient subgroup, SARS-CoV-2 variant and anti-SARS-CoV-2 serology were analysed at baseline. Factors associated with 28-day all-cause hospitalisation were identified using multivariable multilevel logistic regression (MMLR) and summarised with adjusted odds ratio (aOR) and 95% confidence interval (CI). A total of 635 outpatients received mAb: 161 (25.4%) bamlanivimab, 396 (62.4%) bamlanivimab-etesevimab and 78 (12.2%) casirivimab-imdevimab. Ninety-five (15%) patients received full or partial SARS-CoV-2 vaccination. The B.1.1.7 (Alpha) variant was detected in 99% of patients. Baseline serology showed no significant differences among the three mAb regimen groups. Twenty-eight-day all-cause hospitalisation was 11.3%, with a significantly higher proportion ( p 0.001) in the bamlanivimab group (18.6%), compared to the bamlanivimab-etesevimab (10.1%) and casirivimab-imdevimab (2.6%) groups. On MMLR, aORs for 28-day all-cause hospitalisation were significantly lower in patients receiving bamlanivimab-etesevimab (aOR 0.51, 95% CI 0.30–0.88 p 0.015) and casirivimab-imdevimab (aOR 0.14, 95% CI 0.03–0.61, p 0.009) compared to those receiving bamlanivimab. No patients with a history of vaccination were hospitalised. The study suggests differences in clinical outcomes among the first available mAb regimens for treating high-risk COVID-19 outpatients. Randomised trials are needed to compare efficacy of mAb combination regimens in high-risk populations and according to circulating variants.

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Conservation status of the Italian flora under the 92/43/EEC ‘Habitats’ Directive - Giuseppe Fenu; Consolata Siniscalco; Gianluigi Bacchetta; Donatella Cogoni; Maria Silvia Pinna; Marco Sarigu; Thomas Abeli; Elena Barni; Fabrizio Bartolucci; Daniela Bouvet; Annalena Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

Zooming on light packaging waste differences by scanning electron microscopy - Elena Cristina Rada; Gabriela Ionescu; Navarro Ferronato; Marco Ragazzi; Mario Raspanti; Fabio Conti; Vincenzo Torretta (Environmental Science and Pollution Research, 2021)

Comparison of environmental impacts related to municipal solid waste and construction and demolition waste management and recycling in a Latin American developing city - Navarro Ferronato; Luca Moresco; Gabriela Edith Guisbert Lizarazu; Marcelo Antonio Gorritty Portillo; Fabio Conti; Vincenzo Torretta (Environmental Science and Pollution Research, 2021)

Red list of threatened vascular plants in Italy - Simone Orsenigo; Giuseppe Fenu; Domenico Gargano; Chiara Montagnani; Thomas Abeli; Alessandro Alessandrini; Gianluigi Bacchetta; Fabrizio Bartolucci; Angelino Carta; Miris Castello; Donatella Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

Festuca valesiaca Schleich. ex Gaudin newly discovered in the Central Apennines (Italy): a further example of steppe relict in the Abruzzo “dry valleys” - Goffredo Filibeck; Laura Cancellieri; Fabrizio Bartolucci; Ute Becker; Fabio Conti; Samuele Maestri; Marlene Mürz; Elena Schommer; Marta G. Sperandii; Thomas Becker (Plant Biosystems, 2020)

Dispersal ability of threatened species affects future distributions - Michele Di Musciano; Valter Di Cecco; Fabrizio Bartolucci; Fabio Conti; Anna Rita Frattaroli; Luciano Di Martino (Plant Ecology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Detecting Phytogeographic Units Based on Native Woody Flora: A Case Study in Central Peninsular Italy - Marta Latini; Fabrizio Bartolucci; Fabio Conti; Mauro Iberite; Gianluca Nicolella; Anna Scoppola; Giovanna Abbate (The Botanical Review, 2017)

Effects of the increase in neuronal fatty acids availability on food intake and satiety in mice - Roberto Coccurello; Antonio Caprioli; Sara Bellantuono; Francesca R. D’Amato; Roberto Conti; Fabio Giannessi; Franco Borsini; Anna Moles (Psychopharmacology, 2010)

Fusarium head blight evaluation in wheat transgenic plants expressing the maize b-32 antifungal gene - Carlotta Balconi; Chiara Lanzanova; Elena Conti; Tiziana Triulzi; Fabio Forlani; Marzia Cattaneo; Elisabetta Lupotto (European Journal of Plant Pathology, 2007)

Generation and characterization of a mouse lymphatic endothelial cell line - Marina Sironi; Annarita Conti; Sergio Bernasconi; Anna M. Fra; Fabio Pasqualini; Manuela Nebuloni; Eleonora Lauri; Maida De Bortoli; Alberto Mantovani; Elisabetta Dejana; Annunciata Vecchi (Cell and Tissue Research, 2006)

Olive oil, seed oils and other added fats in relation to ovarian cancer (Italy) - Cristina Bosetti; Eva Negri; Silvia Franceschi; Renato Talamini; Maurizio Montella; Ettore Conti; Pagona Lagiou; Fabio Parazzini; Carlo La Vecchia (Cancer Causes & Control, 2002)

Minuartia moraldoi (Caryophyllaceae) , a new species from Cilento (Campania, S. Italy) - Fabio Conti (Plant Biosystems, 2001)

Energy intake and dietary pattern in cancer of the oral cavity and pharynx - Silvia Franceschi; Fabio Levi; Ettore Conti; Renato Talamini; Eva Negri; Luigino Dal Maso; Peter Boyle; Adriano Decarli; Carlo La Vecchia (Cancer Causes & Control, 1999)